Algorithms for computerised monitoring the performance of DCP network - GUPTA, M. K. (MAUSAM, 2001)
India Meteorological Department (IMD) has been operating a network of one hundred Automatic Weather Stations called Data Collection Paltform (DCP) since 1986. All these stations are unmanned and there is no way to know the working status of DCP equipment except to extract such Information from the data transmitted by them. Hence suitable algorithms were developed to evaluate the working status of various sub-systems of DCP stations by analysing the data received from them, which is essential for their effective and efficient maintenance. The concept used in developing these algorithms is described here.